Clinical findings, dental treatment, and improvement in quality of life for a child with Rothmund-Thomson syndrome - Katharina Morant Holanda De Oliveira; Raquel Assed Bezerra Silva; Fabricio Kitazono Carvalho; Lea Assed Bezerra Silva; Paulo Nelson-Filho; Alexandra Mussolino Queiroz (Wolters Kluwer Medknow Publications, 2016)
The purpose of this study was to report the clinical findings, dental treatment, and improvement in quality of life for a child with Rothmund-Thomson syndrome. The patient had alopecia, delayed speech, low weight and height, cholestasis, and iron deficiency anemia. Furthermore, there were carious lesions and darkened spots on all primary molars. Microdontia of a premolar was observed at the radiographic examination. The patient and family had no commitment to her oral health and dental treatment at first appointments. Oral hygiene instructions, composite restorations, endodontic treatments, teeth extractions, and stainless steel crown installations were performed. The patient was followed up for 7 years through the present due to other possible future clinical findings associated with the syndrome. An improvement in social aspects was observed after removal of toothache and improved esthetics. Such patients need continuous periodic services, which contributes to improving the quality of life in both buccal and general aspects.